Diskursus Pembatasan Kekuasaan di Indonesia Dalam Perspektif Konstitusi dan Konstitusionalisme - Erham, Erham; Ma’arij, Aman; Gufran, Gufran (Universitas Batanghari Jambi, 2024)
The purpose of this research is to describe the constitution as the most important legal document. The constitution is a very important rule for every nation and state, both those that have been independent for a long time and those that have just gained their independence. Because the state is an organization of power that includes a very large number of people, it is necessary to have a system of control (an effective system of restrictions). This is done through law (both written and unwritten, namely the constitution or basic laws). This research method is legal research. This article is the result of research on the issue of limiting the power of state government in terms of the constitution and the underlying constitutionalism. The discourse regarding limiting power is an integral part in countries that base themselves on constitutional democracy, such as the Republic of Indonesia, where the constitution actually acts as an instrument or means for regulating and controlling power.The idea that government power needs to be limited because the State is run by humans and that humans are without exception inherent in many weaknesses. His proposition which later became famous reads as follows: